A characterization of chaotic order and a problem. Issue 2 (1998) - Fujii, Masatoshi; Jiang, Jian Fei; Kamei, EiZaburo; Tanahashi, Kotaro
Abstract : In our previous notes, we give a useful characterization of the chaotic order, i.e., log A ≥ log B for positive invertible operatorsA andB . In this note, we present a short proof to the characterization of the chaotic order and give an answer to a related problem on it. Moreover we consider the orders defined byA δ ≥ B ​ δ ( 0 < δ < 1 ) as an interpolation between the chaotic order and the usual order via the Furuta inequality.